PENGGUNAAN MEDIA PERMAINAN MONOPOLI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 3 PEKANBARU - Yanti, Riza Fitri; Holiwarni, Betty; Copriady, Jimmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research about use of media monopoly game has been applied to improve students learning result on the subject of hydrocarbon in class X SMAN 3 Pekanbaru. Form of research is experiment research with randomized control group pretest-posttest design. The population consisted of three classes, that is X1, X2, and X3. The sample used, that is X2 as experiment class and X1 as control class that randomly determined after testing normality and homogeneity. Experiment class was given treatment with using media monopoly game while the control class without use media monopoly game. Analysis of data used t-test. Results of the analysis it was found that tscore > ttable (3,06 > 1,67), it means that the use of media monopoly game can improve students learning result on the subject of hydrocarbon in class X SMAN 3 Pekanbaru. The category improvement of students learning achievement in experiment class was high category (N-gain =0,75) and in control class was medium category (N-gain =0,69).Key Words : Media Monopoly Game, Learning Result, Hydrocarbon